Flood disaster preparedness experiences of hospital personnel in Thailand: A qualitative study - Kanittha Rattanakanlaya (2018)
© 2018 College of Emergency Nursing Australasia Background: Nurses, as well as other health personnel and health systems, worldwide need to be adequately prepared for disasters because it is often difficult to predict where and when disasters strike. The 2011 Thailand flood disaster caused significant damage, including to hospitals. The purpose of this study was to investigate the experiences of hospital personnel regarding flood disaster preparedness in the central region of Thailand. Methods: This qualitative study was conducted using content analysis. Purposive sampling was used to select the participants. Semi-structured interviews were conducted with 15 participants who were doctors, nurses, and persons involved in flood disaster preparedness. Content analysis was used for data analysis. Findings: Two themes and ten subthemes were extracted with regard to flood disaster preparedness. The two themes were maintaining the function of care provision and struggle with preparedness. Personnel realized that preparation levels of their hospital were inadequate and identified the challenges in providing care during and after floods. Conclusions: The finding identified several areas to improve the current state of preparedness of all hospitals that experienced service disruption due to flood disasters. This can help healthcare personnel, hospitals, and healthcare system to enhance flood disaster preparedness so that they can be better prepared.